1999
DOI: 10.1101/lm.6.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Orphanin FQ Suppresses NMDA Receptor-Dependent Long-Term Depression and Depotentiation in Hippocampal Dentate Gyrus

Abstract: We reported previously that orphanin FQ (OFQ) inhibited NMDA receptor-mediated synaptic currents and consequently suppressed induction of long-term potentiation (LTP) in the hippocampal dentate gyrus. This study examines the effect of OFQ on several other forms of long-term synaptic plasticity in the lateral perforant path of mouse hippocampal dentate gyrus. high-frequency train-induced dentate LTP could be reversed by a subsequent low-frequency stimulation. This depotentiation was also attenuated by either OF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Furthermore, NOP receptor activation with N/OFQ or synthetic agonists impairs memory performances in a variety of cognitive tasks in rodents (Sandin et al, 1997;Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Liu et al, 2007;Roozendaal et al, 2007), whereas the deletion of NOP receptor or preproN/OFQ gene produces the opposite effects (Manabe et al, 1998;Higgins et al, 2002;Mamiya et al, 2003). Consistent with these findings, electrophysiological studies showed that N/OFQ potently inhibits synaptic transmission and synaptic plasticity in the hippocampus and the amygdala (Yu et al, 1997;Meis and Pape, 1998;Yu and Xie, 1998;Wei and Xie, 1999; Bongsebandhu-phubhakdi and Manabe, 2007).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, NOP receptor activation with N/OFQ or synthetic agonists impairs memory performances in a variety of cognitive tasks in rodents (Sandin et al, 1997;Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Liu et al, 2007;Roozendaal et al, 2007), whereas the deletion of NOP receptor or preproN/OFQ gene produces the opposite effects (Manabe et al, 1998;Higgins et al, 2002;Mamiya et al, 2003). Consistent with these findings, electrophysiological studies showed that N/OFQ potently inhibits synaptic transmission and synaptic plasticity in the hippocampus and the amygdala (Yu et al, 1997;Meis and Pape, 1998;Yu and Xie, 1998;Wei and Xie, 1999; Bongsebandhu-phubhakdi and Manabe, 2007).…”
Section: Introductionsupporting
confidence: 70%
“…Electrophysiological studies indicate that N/OFQ inhibits synaptic transmission and plasticity in the hippocampus through suppression of glutamatergic function at the NMDA receptor (Manabe et al, 1998;Yu and Xie, 1998;Wei and Xie, 1999;Bongsebandhu-phubhakdi and Manabe, 2007). Based on these findings, we hypothesized that NOP receptors may regulate recognition memory by interacting with NMDA receptor signaling in the hippocampus.…”
Section: Nop and Nmda Receptors Regulate Recognition Memory Formationmentioning
confidence: 99%
“…The NOP receptor is highly expressed in cortical and limbic regions involved in the integration of the emotional responses of anxiety, fear, and stress such as the amygdala, the bed nucleus of the stria terminalis and the septo-hippocampal region, but also in midbrain areas including the periaqueductal gray matter, the locus coeruleus, and the dorsal raphe nucleus (Meunier 1997;Mollereau and Mouledous 2000;Neal et al 1999). NOP receptor activation decreases neuronal excitability (Chee et al 2011;Dawe et al 2010), neurotransmitter release (Cavallini et al 2003;Kawahara et al 2004;Meis 2003;Schlicker and Morari 2000), as well as neuronal plasticity in cortico-limbic structures (Bongsebandhu-phubhakdi and Manabe 2007;Manabe et al 1998;Wei and Xie 1999) and therefore likely acts via inhibition of neural activity. Activation of NOP receptors induces anxiolytic-like and anti-stress effects across multiple species (reviewed in Chiou et al 2007;Duzzioni et al 2011 ;Fernandez et al 2004;Shoblock 2007) whereas blockade of NOP receptors, by genetic (Gavioli et al 2003;Rizzi et al 2011) or pharmacological means (Gavioli et al 2004;Goeldner et al 2010 ;Redrobe et al 2002;Rizzi et al 2007), has antidepressant-like properties in despair and chronic mild stress-induced anhedonia models (Vitale et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While the role of the N/OFQ system in cognition is now well established its mechanisms of action are still poorly understood. Electrophysiological studies reported that N/OFQ suppresses different forms of neuronal plasticity within the hippocampus including long-term potentiation (LTP) and long-term depression (LTD) by antagonizing the function of the glutamatergic NMDA receptor (Bongsebandhu-phubhakdi & Manabe, 2007;Manabe et al, 1998;Wei & Xie, 1999;Yu & Xie, 1998). Accordingly, studies conducted with knockout mice showed that ablation of NOP receptor activity results in increased intrinsic activity of hippocampal NMDA receptor, which was accompanied at the behavioral level by improved learning abilities that could be reverted by the noncompetitive NMDA receptor antagonist, MK-801 (Mamiya et al, 2003).…”
Section: Introductionmentioning
confidence: 99%